ANALISIS KEENGGANAN MAHASISWA DALAM BERBICARA BAHASA INGGRIS DI PRODI BAHASA INGGRIS FKIP UNRI - Angginawati Lingga Ningrum (Jurnal Pendidikan, 2019)
This research is aimed to find out students’ factors and reasons of reluctance to speak English at the English Department FKIP UNRI. This is a descriptive research conducted by survey design. The instrument administered in this research was questionnaire containing 27 close-ended questions and 7 open-ended questions. The population of this research was 113 of the second semester English department students at FKIP UNRI and the sample of this research were IIB class and IIC class of second semester English Department students. The total number of students is 76 students. The collected data were analyzed using likert scale in order to know the factors and reasons of students’ reluctance to speak English. The result of data analysis showed that there are two factor of students’ reluctance to speak English. The first one is language factor which consists of pronunciation, grammar and vocabulary. The second one is psychological factor which consists of lack of confidence, shyness, anxiety and motivation. The reasons of students’ reluctance base on each factor are afraid of being laughed while mispronouncing, difficulty in constructing sentences and using tenses, difficulty in using exact words, afraid of losing face, afraid of being looked as foolish, peer correction and influence of friends. In conclusion, the language factor and psychological factor contribute in the students’ reluctance to speak English at English Department FKIP UNRI. The highest index percentage on pronunciation indicator indicated that the students had problem with their pronunciation in speaking English and the highest index percentage on lack of confidence indicator indicated that the students had lower self-rating in speaking.